Urbanização e clima urbano do bairro Atalaia na cidade de Aracaju/SE - Santos, Bruna Fortes (2016)
Such research aimed to study the urban climate in the neighborhood Atalaia in the municipality of Aracaju, through the vertical integration process that is intensifying in the area. It appears as a neighborhood that has seen significant urban density, a fact that is reflected in the increased number of buildings and reduction in vegetation, leading to concrete surfaces. These changes are critical parameters of thermal contrasts found in the metropolises. The procedures adopted for the development of research were aerofotografias and satellite images provided by INPE and USGS / EROS to carry out the mapping of the evolution of the urban fabric of the neighborhood, to obtain the thermal images of the area and representation and analysis of albedo. Based on revised bibliography were the aims, general and specific routes, in order to analyze the process of urbanization of that neighborhood and its implications on urban climate behavior. To this end, it sought to evaluate the expansion of the urban fabric of the area under study, the shrinkage or expansion of the vegetation cover and albedo. As the study aimed to analyze the likely thermal contrasts in the neighborhood Atalaia, it was considered representative to work with the hottest months of the year, january, february or march and the coldest months, july or august. The time frame selected by the availability of data was restricted to the years 1984-2008-2015, having adopted the method of analysis Climate System Urban Monteiro, focusing on channel called Thermal Comfort. Thermodynamic components of integrative way we were treated with the interpretation of data obtained by correlating the use of land, rising internal temperatures in the urban environment decreased vegetation cover, checking how much vertical integration is influencing the thermal comfort of the neighborhood. According to the obtained data, we see an increase in temperature due to increased urban grid, reduction of green areas, the growth of vertical buildings and appearances of heat islands side of freshness of islands. The albedo analysis results show a correlation between the temperature values, and albedo, leaving clear that in areas where there was a temperature rise of the albedo values were less intense. And in exposed soils, there was also higher albedo compared to other types of use and occupation, and the resulting temperature lower than the constructed area. It is the conclusion to state that the process of urbanization, and verticalization, increased the population density next to the suppression of green areas has affected the local weather neighborhood Atalaia.